Critical Race Theory and the Limits of Relational Theory in Social Work with Women - QUINN, CAMILLE R. (J Ethn Cult Divers Soc Work, 2015)
The authors present a conceptual framework for expanding the use of relational theory with African-American women. Relational theory (RT) informs practice with women but is inadequate in addressing all aspects of culture and identity. RT presumes that all women desire or are able to make therapeutic connections, yet race, gender, and cultural experiences influence their ability to do so. Successful practice with minority women must address racism and its impact. Critical race theory (CRT) that incorporates a solution-focused (SF) approach is well-suited to address the limits of RT. This overview of a CRT/SF approach describes treatment for diverse women that extends RT and enhances effective social work practice to provide culturally sensitive treatment to women.